ACS712 Based Intelligent Solid-State Relay for Overcurrent Protection of PV-Diesel Hybrid Mini Grid - Arefin, A.A. (Institute of Electrical and Electronics Engineers Inc., 2020)
The paper presents an application of ACS712 current sensor based intelligent solid-state relay for line overcurrent protection of solar-diesel hybrid mini DC grid system. The proposed system can sense the overcurrent faults in the DC grid line and also read continuous current from the distribution side and send it to the server through a wireless module after a certain time. Therefore, the condition of the distribution is monitored from the server side simultaneously. Thus, the proposed system ensures the preventive maintenance of mini-grid system. The experimental result shows that proposed system follows the characteristics of standard IDMT relay with additional intelligent feature. Â© 2020 IEEE.